C# 10 Quick Syntax Reference : a Pocket Guide to the Language, APIs, and Library. - Olsson, Mikael (Web programmer) (ITpro collection, 2022)
Discover what's new in C# and .NET for Windows programming. This book is a condensed code and syntax reference to the C# programming language, updated with the latest features of version 10 for .NET 6. You'll review the essential C# 10 and earlier syntax, not previously covered, in a well-organized format that can be used as a handy reference. Specifically, unions, generic attributes, CallerArgumentExpression, params span, Records, Init only setters, Top-level statements, Pattern matching enhancements, Native sized integers, Function pointers and more. You'll find a concise reference to the C# language syntax: short, simple, and focused code examples; a well laid out table of contents; and a comprehensive index allowing easy review. You won't find any technical jargon, bloated samples, drawn-out history lessons, or witty stories. What you will find is a language reference that is to the point and highly accessible. The book is a must-have for any C# programmer. What You Will Learn Employ nullable reference types Work with ranges and indices Apply recursive patterns to your applications Use switch expressions Who This Book Is For Those with some experience in programming, looking for a quick, handy reference. Some C# or .NET recommended but not necessary.